Impact of alkaline phosphatase on clinical outcomes in patients with ischemic stroke: a nationwide registry analysis - Wang, Zhaobin; Li, Jing; Jing, Jing; Zhang, Zhe; Xu, Qin; Liu, Tao; Lin, Jinxi; Jiang, Yong; Wang, Yongjun; Wang, Anxin; Meng, Xia (Frontiers in Neurology, 2024)
Background: Data on the association between serum alkaline phosphatase (ALP) levels and clinical outcomes in patients with ischemic stroke (IS) is inconsistent and limited. Therefore, this study aimed to investigate the correlation between ALP and prognosis in patients with IS. Methods: Patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) from the Third China National Stroke Registry were divided into four groups according to the quartiles of serum ALP levels on admission. Cox proportional hazards and logistic regression models were used to evaluate the correlation between ALP and the risk of all-cause mortality, disability (modified Rankin Scale (mRS) score 3-5), and poor functional outcomes (mRS score 3-6). Results: The study included 11,405 patients. Higher levels of ALP were associated with all-cause mortality at 3 months (adjusted hazard ratio (HR) per standard deviation (SD): 1.16; 95% confidence interval (CI): 1.07-1.27; P = 0.001) and 1 year (adjusted HR: 1.11; 95% CI: 1.03-1.20; P = 0.010). At the 3-month follow-up, each SD increase of ALP was associated with 12% and 14% higher risk of disability (adjusted odds ratio (OR): 1.12; 95% CI: 1.06-1.18; P < 0.001) and poor functional outcomes (adjusted OR: 1.14; 95% CI: 1.08-1.20; P < 0.001). Similar results were observed at the 1-year follow-up. Higher ALP levels were associated with an increased risk of all-cause mortality, disability, and poor functional outcomes in patients with "others" subtypes (including other determined etiology and undetermined etiology) (P < 0.05). Conclusions: Elevated ALP levels were associated with an increased risk of allcause mortality, disability, and poor function outcomes in patients with IS. Heterogeneity was observed among the subtypes of different etiologies.